SAE Technical Paper Series 2006
DOI: 10.4271/2006-01-3298
|View full text |Cite
|
Sign up to set email alerts
|

Fast Prediction of HCCI Combustion with an Artificial Neural Network Linked to a Fluid Mechanics Code

Abstract: We have developed an artificial neural network (ANN) based combustion model and have integrated it into a fluid mechanics code (KIVA3V) to produce a new analysis tool (titled KIVA3V-ANN) that can yield accurate HCCI predictions at very low computational cost. The neural network predicts ignition delay as a function of operating parameters (temperature, pressure, equivalence ratio and residual gas fraction). KIVA3V-ANN keeps track of the time history of the ignition delay during the engine cycle to evaluate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 28 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…The autoignition integral was previously used to study knock in SI engines with a high degree of success [18]. More recently, it has been applied to HCCI research to study ignition timing, since HCCI is controlled by autoignition [19,20]. This research uses the autoignition integral, with the assumption that the mass in the cylinder follows a self-similar temperature contour, to predict ignition phasing of different temperature zones.…”
Section: Introductionmentioning
confidence: 99%
“…The autoignition integral was previously used to study knock in SI engines with a high degree of success [18]. More recently, it has been applied to HCCI research to study ignition timing, since HCCI is controlled by autoignition [19,20]. This research uses the autoignition integral, with the assumption that the mass in the cylinder follows a self-similar temperature contour, to predict ignition phasing of different temperature zones.…”
Section: Introductionmentioning
confidence: 99%
“…This hysteresis method is necessary because the timescales associated with soot formation tend to be much longer than those of combustion chemistry. Furthermore, it should be noted that the concept of tracking the time history was also used by Aceves et al [49] for fast prediction of HCCI combustion with an ANN linked to the KIVA3V fluid mechanics code. In addition, in the work of Christo et al [28], in order to reduce the dependency of the ANN model on the selection of training sets for modeling turbulent flames, the input parameters were integrated over a prescribed reaction time.…”
Section: Methodsmentioning
confidence: 99%
“…The review of turbulence combustion models can be found in [23], but if the ignition is formally considered as the process preceding the combustion stage, such models are not used in the ignition description. The most effective separation of ignition and combustion stages is realized in [24] based on the usage of ignition integral calculated with the help of an artificial neural network (ANN) and KIVA-3 V (or KIVA4) code. The ignition integral:…”
Section: Turbulent Combustion Modelingmentioning
confidence: 99%